Enterprise bankruptcy in Lithuania - Garškiene, Aldona; Garškaite, Kristina (Journal of Business Economics and Management, 2004)
Since the re‐establishment of the independence, Lithuania has undergone major changes in the sphere of economy and had to re‐orientate it towards a new (economic) market system, to enter new markets, and to restructure the economy. The shift in business conditions has given rise to numerous upheavals, including the bankruptcy of enterprises, which had detrimental economic and social consequences (one of such evils was increasing unemployment). However, it is also necessary to point out the positive role of the bankruptcy, which is related to a growing competition in the contemporary market economy and the acceleration of changes allowing the best companies alone to survive on the market. A positive improvement in the legal basis of bankruptcy and restructuring leaves the hope that the number of bankrupt companies will decrease. Moreover, in order to reduce the bankruptcy risk, it is necessary to create a system of bankruptcy prevention. First Published Online: 14 Oct 2010